Patient Characteristics on Satisfaction with Healthcare Quality in a Teaching Hospital in Nepal - Dangol, Sonu; Mishra, Ravindra (Baneshwor Campus Journal of Academia, 2024)
This study aimed to examine the relationship between patient demographics (gender, age) and service factors (number of hospital visits) on patient satisfaction with healthcare quality in a teaching hospital in Nepal. A quantitative cross-sectional study was conducted using a convenience sample of 40 patients attending the hospital. Data was collected using a questionnaire to assess satisfaction across various dimensions of care. The sample mainly comprised younger females attending the hospital for the first time. Most patients reported average satisfaction with sense of wellbeing, treatment received, staff skills and information provided. No significant correlations were found between gender, age, number of visits and overall satisfaction (p>0.05). Patient demographics and prior hospital experience did not significantly influence satisfaction levels in this study. However, scope remains for improving various quality domains to enhance patient experience. Further research with a larger sample is needed to better understand drivers of satisfaction in the Nepalese healthcare context.